"Connecting to the Ideologies That Surround Us": Oral History Stewardship as an Entry Point to Critical Theory in the Undergraduate Classroom. (1st September 2017) - Nunes, Charlotte
Abstract: In this article I argue that oral history stewardship, as a mode of digital archival practice, offers a useful entry point into understanding and engaging with critical theory in the humanities. I survey recent scholarship to propose that the practical conditions of digital oral history archiving inform the most theoretically engaged work in the field of archival practice today. Through a discussion of a collaboration between the spring 2015 undergraduate English class I taught at Southwestern University and the Texas After Violence Project (TAVP) oral history collection at the University of Texas Libraries Human Rights Documentation Initiative (HRDI), I argue that in a higher-education setting, the practical experience of digital archival stewardship clarifies a theoretical understanding of the features of responsible community engagement.